Health and quality of life: the impacts of Covid-19 on family farming (Research, Society and Development, 2023)
This article has the objective of analyzing the impacts of Covid-19 on the health and quality of life of two family farmers and producers in Brazil. The method that was used was a bibliographic review. For the search for two jobs, descriptors were used to cover aspects related to the health dimensions and way of life related to small producers and farmers. In the question of health and way of life, the impacts are about the difficulty of serving the rural population. Climatic and geographical issues, such as the rainy season in the Amazon, will affect river transportation and land transit, thus making it difficult for professionals, users, and inputs to circulate, creating numerous challenges to access to services. I verified that the pandemic reinforced the situations of social vulnerability and the patterns of inequality and exclusion of farmers and producers of family farming, in addition, the pandemic brought emotional instability generating discomfort, conflicts and questions. The pandemic exacerbated our structural deficiencies in the sanitary quest, challenging our ability to contain the contamination of Covid-19. The message of the UN is clear: water, sanitation and hygiene are essential in mitigating and not confronting viruses. It is about a reconstruction of the right to health through the supply and availability of adequate water and sanitation that respect, protect and fulfill aspects of the right to water, as a means of safeguarding health, as a fundamental right and of human dignity.